Proceedings of the 3rd International Seminar on Non-Ideal Compressible Fluid Dynamics for Propulsion and Power NICFD 2020. - Pini, Matteo; De Servi, Carlo; Spinelli, Andrea; Di Mare, Francesca; Guardone, Alberto (Spinger, 2021)
This book contains a collection of the main contributions from the third edition of the NICFD conference, organized by the Special Interest Group on Non-Ideal Compressible Fluid Dynamics (SIG-49). It provides insight on the latest research findings in the field of NICFD that are relevant to a number of engineering applications related to the conversion of renewable and waste energy sources, like organic Rankine cycles, supercritical CO2 cycle power plants, combustors operating with supercritical fluids, and heat pumps. The various chapters of the book document research encompassing theoretical, computational, and experimental aspects of the gas dynamics of non-ideal reactive and non-reactive flows and their impact for the design of internal flow components (turbomachinery, heat exchangers, combustors). Since the accurate calculation of fluid thermo-physical properties is of great concern in NICFD, all the chapters address this problem by describing state-of-the-art models for the characterization of the properties of pure fluids and mixtures.